Implementation Of The Integrated Referral Service System (Slrt) For Poverty Alleviation In The Social Service Office Of Pinrang Distric - Sri Ayu Lestari; Aslinda; Novayanti Sopia Rukmana; Ismail; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2025)
This study aims to determine the Content of Policy and Context of Implementation and to determine the impact of the implementation of the Integrated Referral Service System (SLRT) program at the Pinrang Regency Social Service. Descriptive qualitative research type. Data collection techniques through observation, interviews and documentation. The data analysis technique includes data condensation, data presentation, and data verification. The results showed that the policies affected in the Integrated Referral Service System (SLRT) program are people who cannot afford it. The types of benefits generated are free BPJS assistance, social assistance in the form of PKH and BPNT and money and assistive devices for people with disabilities, and KIP assistance. In the flow of proposing community names to be included in DTKS, it is necessary to process data collection of community names proposed by the village / kelurahan, then deliberated by village / kelurahan officials, after which the minutes are uploaded in the SIKS-NG application. Then the Social Service Office will approve and certify and then send it to the Center, in this case the Ministry of Social Affairs, which determines the final result. The resources used are human resources including the Head of the Social Service, Social Service Managers, Facilitators, Puskesos / Operators and Village / Sub-district officials, and Front Office. The budget sources obtained come from the APBN and APBD and assistance from institutions that work with the Social Service. In the disbursement of names in DTKS, you can check the social assistance check application, while for BPJS deactivation, a letter will be sent or given to the person concerned. The impact felt by the community shows the impact of changes experienced by the community when receiving assistance even though it is only to meet basic needs such as in the education sector, health sector, social protection and social assistance.